The Architecture of Fiqh Muamalat Based on The Geometry of Equilibrium in the Islamic Tourism Ecosystem - Riyanto Sofyan; Ida Busnetty; Aa Hubur; Soeharjoto Soeharjoto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The massive growth of the global Muslim travel market demands a rigorous business governance model. While Indonesia has integrated Muslim-friendly tourism into RPJMN 2025–2029 via Perpres No. 12/2025, a legal vacuum persists following the revocation of Permenparekraf No. 2/2014, leading to policy fragmentation and